ANALISIS PENGARUH BIAYA PRODUKSI, LUAS LAHAN DAN HARGA JUAL TERHADAP PENDAPATAN PETANI KELAPA SAWIT DI DESA RAMBAH JAYA - Imroatul Khasanah; Heffi Christya Rahayu; Seprini Seprini (Jurnal Ekonomi Bisnis Kompetif, 2026)
This study aims to determine the effect of production costs, land area, and selling prices on the income of oil palm farmers in Rambah Jaya Village. This study applies a quantitative approach by collecting primary data through distributing questionnaires to 50 oil palm farmers who were used as respondents. The sampling technique was carried out using the simple random sampling method. Data analysis was carried out using data quality tests, descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing processed using the SPSS program. The results of the study indicate that partially production costs do not significantly affect the income of oil palm farmers, while land area and selling prices have a positive and significant effect on the income of oil palm farmers. Simultaneously, production costs, land area, and selling prices together have a significant effect on the income of oil palm farmers. This study is expected to be a consideration for farmers and related parties in efforts to increase income.